Comparation Body Weight, Body Length, Kidney Weight and Liver Weight between Indonesian Adult and Thailand Adult in Autopsy Cases in Sardjito Hospital June 2011 to June 2012 - Wikan Basworo; Idha Arfianti Wira Agni (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2014)
This research aims to retrospectively review forensic autopsy cases of a Indonesian people to see the description of liver weight, kidney weigt, body weight  and length. The present study included 8 cases autopsies from Sardjito Hospital from June 2011  to  June 2012. The subjects were  from unnatural death following criteria. The weighed organs included  liver and kidneys.We compared the result with Thailand population with independent sample t-test, to see the differences between them. The ages ranged from 16 to 69 years and there were 2  males and 6  females. The Mean were represented by; 55,1; 153,1; 1094,5; 103,6  in body weight, body  length, liver weight, and kidneys weigth respectively. There were no significant differences between Indonesian dan Thailand people in age, body weight, and body height. There were differences between Indonesian dan Thailand people in liver weight and kidney weight, but significancy can not be analyzed because lack of comparison data. There were no significant differences in body weight, body  length, liver weight, and kidneys weigth between autopsy cases  from Sardjito Hospital from June 2011  to  June 2012 with Thailand publication paper.